Solar Irradiance Variability: Modeling the Measurements. Issue 8 (26th August 2020) - Lean, J. L.; Coddington, O.; Marchenko, S. V.; Machol, J.; DeLand, M. T.; Kopp, G.
Abstract: New models of the Sun's irradiance variability are developed from 15 years of direct observations made by the Solar Radiation and Climate Experiment (SORCE) spacecraft from 2003 to 2017 (inclusive). Multiple linear regression parameterizes the observations in terms of facular brightening and sunspot darkening, which are the primary sources of solar irradiance variability. The facular influence is specified as a combination of a linear and nonlinear solar ultraviolet (UV) index; the addition of the nonlinear term allows better reproduction of concurrent solar cycle and rotational variability. The sunspot darkening index is calculated using sunspot observations from both the Debrecen catalog and Air Force Solar Observing Optical Network (SOON) operational sites, the former providing superior model performance. The new model of total solar irradiance variability, NRLTSI3, with the Debrecen sunspot index reproduces the direct Total Irradiance Monitor (TIM) observations better than does the NRLTSI2 model that currently specifies irradiance for the NOAA Climate Data Record (CDR); the correlation of the model and observations increases from 0.956 to 0.971, and the standard deviation of the residuals decreases from 0.124 to 0.100 W m −2 . The new model of solar spectral irradiance variability, NRLSSI3, which extends from 115 to 100, 000 nm, reproduces rotational modulation in independent Ozone Monitoring Instrument (OMI) observations at near‐UV and visible wavelengths. The SATIRE model overestimates rotational modulation of near‐UV Fraunhofer spectral features because of excess facular brightness; the EMPIRE model overestimates rotational modulation at all near‐UV wavelengths. Key Points: New models of solar irradiance variability, NRLTSI3 and NRLSSI3, are constructed from SORCE observations using improved facular and sunspot inputs OMI observations validate the new model during solar rotation; SATIRE and EMPIRE models overestimate this variability Faculae and sunspots may be less bright in the UV spectrum than SATIRE's theoretical stellar atmosphere model prescribes